19F Magnetic Resonance Imaging and Spectroscopy in Neuroscience. (15th October 2021) - Modo, Michel
Highlights: Discussion of technical challenges in using 19 F MRI. Provides overview of 19 F MRI/MRS in neuroscience. Lists of fluorine-based contrast agents, blood substitutes, anesthetics and pharmaceutical drugs. Abstract: 1 H magnetic resonance imaging (MRI) has established itself as a key diagnostic technique, affording the visualization of brain anatomy, blood flow, activity and connectivity. The detection of other atoms (e.g. 19 F, 23 Na, 31 P), so called hetero-nuclear MRI and spectroscopy (MRS), provides investigative avenues that complement and extend the richness of information that can be gained from 1 H MRI. Especially 19 F MRI is increasingly emerging as a multi-nuclear ( 1 H/ 19 F) technique that can be exploited to visualize cell migration and trafficking. The lack of a 19 F background signal in the brain affords an unequivocal detection suitable for quantification. Fluorine-based contrast material can be engineered as nanoemulsions, nanocapsules, or nanoparticles to label cells in vitro or in vivo . Fluorinated blood substitutes, typically nanoemulsions, can also carry oxygen and serve as a theranostic in poorly perfused brain regions. Brain tissue concentrations of fluorinated pharmaceuticals, including inhalation anesthetics (e.g. isoflurane) and anti-depressants (e.g. fluoxetine), can also be measured using MRS. However, the low signal from these compounds provides a challenge for imaging. Further methodological advances that accelerate signal acquisition (e.g. compressed sensing, cryogenic coils) are required to expand the applications of 19 F MR imaging to, for instance, determine the regional pharmacokinetics of novel fluorine-based drugs. Improvements in 19 F signal detection and localization, combined with the development of novel sensitive probes, will increase the utility of these multi-nuclear studies. These advances will provide new insights into cellular and molecular processes involved in neurodegenerative disease, as well as the mode of action of pharmaceutical compounds.